2021
DOI: 10.1111/are.15222
|View full text |Cite
|
Sign up to set email alerts
|

Taurine supplementation enhances the replacement level of fishmeal by soybean concentrate in diets of juvenile Pacific white shrimp ( Litopenaeus vannamei Boone, 1931)

Abstract: This study aimed to evaluate the effects with and without 1000 mg taurine supplement and five levels (0%, 25%, 50%, 75% and 100%) of fishmeal (FM) replaced by soybean concentrate (SBC) in the diet on white shrimp. After 8-weeks' feeding, the results showed that the taurine supplement significantly affected final weight (FW), weight gain (WG%), feed intake (FI%), glutamate-pyruvate transaminase (GPT), triglyceride and cholesterol in plasma and glutathione peroxidase (GPx) in haemocytes of white shrimp. There is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 68 publications
6
9
0
Order By: Relevance
“…The increasing dietary lipid increased the HSI of white shrimp, which was similar to previous studies of white shrimp that HSI values increased gradually with increasing dietary lipid level (Hu et al, 2008;Xu et al, 2018), but the taurine supplement did not significantly affect the HSI of white shrimp in this study, similar to a previous study on white shrimp with taurine supplement (To & Liou, 2021).…”
Section: Discussionssupporting
confidence: 92%
See 4 more Smart Citations
“…The increasing dietary lipid increased the HSI of white shrimp, which was similar to previous studies of white shrimp that HSI values increased gradually with increasing dietary lipid level (Hu et al, 2008;Xu et al, 2018), but the taurine supplement did not significantly affect the HSI of white shrimp in this study, similar to a previous study on white shrimp with taurine supplement (To & Liou, 2021).…”
Section: Discussionssupporting
confidence: 92%
“…In this study, increases in dietary lipids and taurine supplements resulted in significant increases in lipid contents of whole body and muscle of white shrimp, showing excess dietary lipids deposited in the tissue, which was similar to the previous studies of dietary lipid levels on white shrimp (Hu et al, 2008;Liu et al, 2018) and taurine supplements in the diet on white shrimp (To & Liou, 2021;Yue et al, 2013). We did not analyse lipid content in the hepatopancreas of white shrimp in the present study, but a previous study reported that lipid content in the whole body was related to the HSI value, which meant that the high HSI value of white shrimp recorded high lipid content in the whole body because most lipids of white shrimp were stored in the hepatopancreas (Xu et al, 2018).…”
Section: Discussionssupporting
confidence: 91%
See 3 more Smart Citations